Study of Physiology and Some Biochemical Parameters in Infected People (Eurasian Journal of Research, Development and Innovation, 2024)
This study was conducted in the laboratories of Al-Hakim Hospital Artificial Kidney Department in Najaf Governorate for the period from 1/2/2024 to 4/10/2024 with the aim of finding the relationship between some biochemical parameters and kidney disease in affected males. Blood samples were examined for (30) male patients entering the above-mentioned department who suffer from incapacitating kidney disease. The results were compared with the control group, which included (30) healthy males. After conducting the necessary tests, the following was found . : A study of one of the physiological blood parameters showed a significant decrease (P